PENGGUNAAN MAJAS METAFORA DAN SIMILE DALAM KUMPULAN PUISI KUJILAT MANIS EMPEDU - Ardhita, Wenny Indah; Hermawan, Wawan; Fatoni, Akhmad (Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to examine the use of metaphors and similes in the collection of modern Indonesian poetry